Legal Accountability of Digital-Banking Errors in Electronic Payment Systems Based on Real Transaction-Failure Data (Scientific Journal of Research Studies in Future Human Sciences, 2025)
Digital banking infrastructures have transformed payment ecosystems in Iran through the rapid expansion of electronic transaction channels, yet the frequency and complexity of transaction disruptions have simultaneously intensified legal debates about liability for service failures. Real operational data collected from national payment networks between 2019 and 2023 indicate significant fluctuations in transaction success rates, delays in settlement cycles, and intermittent interruptions across POS terminals, online gateways, and mobile payment applications. These disruptions have produced measureable financial and non-financial harm to users, ranging from temporary unavailability of funds and duplicate withdrawals to denied transactions despite successful debits. Such failures have renewed the need to clarify standards of care, evidentiary thresholds, and the scope of civil liability governing banks and payment service providers. The purpose of this article is to analyse the legal responsibility of digital banking institutions for transactional errors within electronic payment systems using empirical findings derived from actual disruption records reported in recent national datasets. The study first situates digital transaction errors within the broader architecture of banking digitalization, highlighting how infrastructural interdependence between banks, payment processors, and clearing systems affects the attribution of liability. It then examines current doctrinal approaches to fault, causation, and compensation in Iranian civil law and compares them with contemporary financial technology jurisprudence reported in peer-reviewed studies. The methodological framework integrates a doctrinal legal analysis with empirical interpretation of operational payment-performance indicators, allowing the identification of patterns of failure that have direct implications for liability formation. Findings demonstrate that transaction-error liability is shaped by a combination of system-level vulnerabilities, inadequate service-level commitments, insufficient transparency in transaction traceability, and the lack of unified evidentiary standards acceptable across courts and regulatory bodies. The study concludes by proposing a structured model of liability classification for digital-banking errors based on verifiable transaction-disruption metrics. Such a model can support courts, regulators, and financial institutions in determining responsibility with greater precision, reducing dispute duration, and improving user protection within the rapidly evolving environment of electronic payments.